Between papers and peril: Pakistani asylum narratives in Italy’s new migration moment - Hussain, Zubair; Ullah, Ihtisham (Journal of International Students, 2026)
This article examines how Pakistani men seeking protection in Italy make sense of leaving home, enduring irregular journeys, and rebuilding their lives under “paperwork time.” Drawing on ten in-depth, note-based interviews conducted across different stages of the asylum process, we apply reflexive thematic analysis to explore how migration decisions, danger, and belonging are narrated under high-stakes credibility pressures. The participants’ accounts rarely fit a simple refugee/economic binary: they describe layered motives shaped by family obligation, status aspirations, economic pressure, and, for some, chronic insecurity. Journeys are recalled as organized deprivation structured by debt and coercion, including hunger, unsafe water, injury, and threats by intermediaries. Arrival does not end hardship; it often transforms it into prolonged waiting, language dependence, precarious work, and loneliness. A central finding is that asylum operates as a narrative regime.